The Dominus Litis Advocate who Handles Debt Law Cases - Panggabean, Ruben; Mansar, Adi; Nadirah, Ida (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
An advocate is a lawyer who practices law through the power of attorney (volmacht) granted by clients, both persons and legal entities, both inside and outside of the courtroom. The range of legal services includes advising, assisting, exercising power of attorney, representing, defending, and taking other legal actions on behalf of their clients. The advocate is free to choose whether his client's case will be settled out of court (non-litigation) in the course of his work, particularly in the area of debt settlement. This area is governed by the Indonesian Advocate Code of Ethics and is known as the dominus litis principle. However, in order to exercise the authority, the advocate must possess financial knowledge in order to offer the client a case settlement plan as legal justification, allowing the client to accept legal counsel from his advocate to pursue an out-of-court settlement. Through training and certification programs coordinated and organized with the National Competency Certification Agency (BNSP), the Advocate Organization bears the responsibility of enhancing the expertise of advocates in addition to themselves. An advocate with greater expertise will be less likely to violate the advocate code of ethics while also providing clients with the best possible protection as recipients of legal services. Rather than creating more issues for their customers, advocates become part of the solution (problem solver).